PKM PENINGKATAN PENGETAHUAN PEDAGOGIK, KEMAMPUAN REFLEKTIF, KECERDASAN EMOSIONAL, POLA KOMUNIKASI INSTRUKSIONAL DAN KOMPETENSI PEDAGOGIK - Susanto, Ratnawati; Yumeldasari, Yumeldasari; Rozali, Yuli Azmi (Universitas Esa Unggul, 2021)
The concept of the Pedagogical Competency Development Model (PTUPT, 2019-2021) is a new pedagogic paradigm that has a significant level for alleviating the problem of teacher pedagogical competency development in DKI Jakarta. The purpose of community service is carried out within the framework of meeting the needs of the two research partners at SDN Duri Kepa 03 and SMP Al - Chasanah towards increasing pedagogic knowledge, reflective abilities, emotional intelligence, instructional communication patterns and pedagogical competencies and implementation is carried out within the framework of the Independent Learning Campus policy research program Independence and community service based on PTS research results. The implementation method is carried out by testing knowledge through a computer program based on a web-based pedagogic competency measurement system, socialization, training, self-evaluation, reflective, exploration, practice by playing video recordings of models, model application pocket books, model strategy books, simulations, sharing knowledge and experiences, interviews and coaching, Talent Search Matrix. The results obtained show that: (1) there is an increase in knowledge and skills on the five dimensions with indicators 75% of teachers and with an effectiveness level of 75%, (2) 75% of teachers giving opinions on The questionnaire stated that the average community service program was at an effectiveness level of 75%. Keywords: Pedagogical Competency Development Model, New Pedagogic Paradigm, Talent Search Matrix.